Detection of Enterocytozoon hepatopenaei (EHP) DNA in the polychaetes from shrimp ponds suffering white feces syndrome outbreaks - Desrina Desrina; Slamet Budi Prayitno; Alfabetian Harjuno Condro Haditomo; Rusthesa Latritiani; Sarjito Sarjito (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Desrina, Prayitno S B, Haditomo A H C, Latritiani R, Sarjito S. 2020. Detection of Enterocytozoon hepatopenaei (EHP) DNA in the polychaetes from shrimp ponds suffering white feces syndrome outbreaks. Biodiversitas 21: 369-374. Enterocytozoon hepatopenaei (EHP) is the newly emerging pathogen of farmed shrimp in Asia. EHP was associated with white feces syndrome (WFS) in shrimp because the spores existed in the feces of shrimp with WFS. Polychaetes are benthic invertebrates and potential to contribute to EHP outbreaks in a pond by acquiring the pathogen and transfer it to shrimp upon feeding. The objective of this study was to determine (1) the occurrence of EHP in polychaetes with Giemsa staining of the coelomic fluid, 1-step PCR and histopathology and (2) to determine pathological changes of EHP infected tissues. Polychaetes were obtained from 20 shrimp ponds located in 9 districts along the North Coast of Java Island, Indonesia. There were no EHP spores detected in the stained coelomic fluid. The 1-step PCR analysis was able to detect the EHP DNA (prevalence was 10%). The Alignment of EHP DNA sequence found in polychaetes showed 100% identity with a published sequence. Histopathological examination showed hypertrophy cells and nuclei, however, no EHP mature spores were found in the epithelial cells on the mucosal layer of the stomach and intestines. Although methods used did not give the convergence results, however, a result of PCR and sequence analysis showed that EHP occurred in the polychaetes in the WFS infected ponds at low point prevalence.